(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The presentation analyzes the situation of rural education in Colombia, identifying limitations such as school dropouts, lack of resources, corruption, quality, little belonging, inequality and exclusion. In addition, it seeks: What factors are limiting the current situation of rural education in Colombia? To answer this question, the following general purpose of the work is taken into account: analyze and reflect on the solutions that rural education in Colombia can have from a comprehensive and collaborative perspective. To do this, a bibliographic review was carried out in Redalyc and Google academic.